2016
DOI: 10.2489/jswc.71.6.484
|View full text |Cite
|
Sign up to set email alerts
|

Cattle use of perennial streams and associated riparian areas on a northeastern Oregon landscape

Abstract: Stream and riparian health is a major concern for state and federal land management agencies that are charged with oversight of extensive land holdings in the mountain west of the United States. Several federal agencies in the 1980s and 1990s determined that livestock grazing had adversely impacted a majority of federal lands in this region. In response, management was changed on grazing allotments to focus on stream system health. Recent advanced global positioning system (GPS) logging capabilities, both accu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 23 publications
0
1
0
Order By: Relevance
“…The average daily distance traveled which was estimated in this study (~5 km) is similar to the one observed by Johnson [34]. It was discovered by tracking grazing cattle in every-second intervals using GPS collars.…”
Section: Animal Activitysupporting
confidence: 87%
“…The average daily distance traveled which was estimated in this study (~5 km) is similar to the one observed by Johnson [34]. It was discovered by tracking grazing cattle in every-second intervals using GPS collars.…”
Section: Animal Activitysupporting
confidence: 87%
“…Meadow scale results confirm the importance of adaptively managing annual grazing pressure on individual meadows within allotments (Clary 1999 ; Freitas et al 2014 ; George et al 2011 ) even when allotment stocking rates are relatively low. Grazing management and distribution strategies (e.g., off stream water development) can be effective in limiting cattle use of sensitive habitats like riparian areas (Johnson et al 2016 ). Implementation and monitoring of livestock grazing distribution strategies to meet riparian grazing standards in all meadows within allotments is key to obtaining conservation objectives.…”
Section: Discussionmentioning
confidence: 99%